Perceived Quality of Food Service System and Food Culture (Kembul) in Children Penitentiary Class IA, Blitar Regency - Yurike Dhika Adhela; Trias Mahmudiono; Stefani Verona Indi Andani (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2020)
Background: The foodservice system in Children Penitentiary is an action for fulfilling the nutritional needs of prisoners. Lack of nutrition that is not by the standard, will result in the occurrence of nutritional problems and reduce the health status for prisoners during the coaching period. One indicator for better quality access to food services is to explore how the perceptions of prisoners on food services which are provided by the institution. Objective: The aims of this study was to determine the perceptions of inmates on the quality of service and provision of food at the Children Penitentiary Class IA, Blitar Regency. Method: This study used a qualitative approach with a semi-structured deep interview and observation method to explore data deeply and holistically. The informants consisted of 10 people and the criteria for key informants were between age range from 15 until 20 years old. Result: The results of the study showed that there were factors that influenced the perception of food quality assessment in LPKA, including internal factors, such as the emergence of eating behaviour and formation of eating culture among other prisoners. Besides assessment, there also included the taste of food, a portion of food, variety of menus, food hygiene, also the food from visitors or family. Conclusion: Eating behavior among prisoners forms a new culture in the scope of Class IA LPKA Blitar, which is a culture of joint eating or "kembul" which creates a sense of family among prisoners.